2014
DOI: 10.1111/1469-0691.12541
|View full text |Cite
|
Sign up to set email alerts
|

Association between serological evidence of past Coxiella burnetii infection and atherosclerotic cardiovascular disease in elderly patients

Abstract: Q fever, caused by Coxiella burnetii, may cause vascular complications, but the role that this infection may play in the development of atherosclerotic cardiovascular disease remains unknown. This study examined the association between Q fever serology and cardiovascular disease in a region where Q fever is endemic. A case-control study was conducted in the Hospital Universitario de Burgos (Spain) between February 2011 and June 2012. A total of 513 samples were tested, from 454 hospitalized patients ≥65 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…In this study, the patients who had acute Q fever had a higher risk of suffering from a cerebrovascular accident and ischaemic heart disease after 12 years. Following this line of research , our group has recently demonstrated an association between serological markers consistent with past infection by C. burnetii and cardiovascular disease in elderly hospitalised patients from a region where the infection is endemic [23 ]. However, it is unknown whether persistent infection may act in a similar way, and if any subtype of cardiovascular disease may be particularly involved in this association.…”
Section: Discusionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the patients who had acute Q fever had a higher risk of suffering from a cerebrovascular accident and ischaemic heart disease after 12 years. Following this line of research , our group has recently demonstrated an association between serological markers consistent with past infection by C. burnetii and cardiovascular disease in elderly hospitalised patients from a region where the infection is endemic [23 ]. However, it is unknown whether persistent infection may act in a similar way, and if any subtype of cardiovascular disease may be particularly involved in this association.…”
Section: Discusionmentioning
confidence: 99%
“…Details of the recruitment and patient selection have been published previously [23]. The current study is an extension of previous one, focusing on ischaemic stroke and persistent or chronic C.burnetti infection, and conducted by expanding the sample (454 to 634 patients according to the size of the sample calculated), serology (antibody titres IgG phase I against Q fever), and new secondary data.…”
Section: Patients: "Association Between Serological Evidence Of Past mentioning
confidence: 99%
See 1 more Smart Citation
“…We thank D. Chatzidimitriou et al for their letter about our article [1]. It refers to the controversies that have arisen over the years in this field.…”
mentioning
confidence: 96%
“…We are grateful to Gonzalez-Quijada et al [1] for providing novel insight into the long-lasting infection hypothesis in their study. Bearing in mind that several controversies have arisen over the years in this field, we believe that some issues need to be further clarified before safe conclusions can be reached.…”
mentioning
confidence: 96%